2010
DOI: 10.1103/physrevb.82.165422
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Mn layers on Rh(001): Investigations using scanning tunneling microscopy and density functional calculations

Abstract: The structural and magnetic properties of ultrathin layers of Mn grown on Rh͑001͒ surfaces have been investigated using scanning tunneling microscopy ͑STM͒ and ab initio density-functional calculations. STM shows perfect wetting of the Rh substrate by the first Mn monolayer ͑ML͒ accompanied by a high mobility of the Mn atoms and only little film-substrate intermixing. By way of contrast, the second monolayer is unstable against formation of multilayer islands at 300 K. However, this is only a transient effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…27,28 For the thicker Mn films, the presence of slight tetragonal distorted fct states (i.e., c/a ∼ 0.96 and c/a ∼ 1.05 for the former and latter cases) was suggested to be accompanied by two antiferromagnetic ground states of in-plane c(2×2) and layered AFM, respectively, as below the bulk Néel temperature of about 540 K. 30,35,36 Interestingly, as mentioned earlier, the ground-state energies of in-plane c(2×2) and layered-AFM states could become degenerate for a fcc Mn. 23,24 In such scenario, fcc-Mn film could reveal novel magnetic properties. For example, a perpendicular magnetic anisotropy was found to be established in 6 ML Fe/fcc-Mn bilayers while the thickness of fcc-Mn ultrathin film is thicker than 2 ML and at low temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 For the thicker Mn films, the presence of slight tetragonal distorted fct states (i.e., c/a ∼ 0.96 and c/a ∼ 1.05 for the former and latter cases) was suggested to be accompanied by two antiferromagnetic ground states of in-plane c(2×2) and layered AFM, respectively, as below the bulk Néel temperature of about 540 K. 30,35,36 Interestingly, as mentioned earlier, the ground-state energies of in-plane c(2×2) and layered-AFM states could become degenerate for a fcc Mn. 23,24 In such scenario, fcc-Mn film could reveal novel magnetic properties. For example, a perpendicular magnetic anisotropy was found to be established in 6 ML Fe/fcc-Mn bilayers while the thickness of fcc-Mn ultrathin film is thicker than 2 ML and at low temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Among the metallic antiferromagnets, Mn films are regarded as highly interesting systems due to abundant magnetic phases that are strongly correlated with the crystalline structures. 23,24 It has been theoretically suggested that the face-centered-cubic (fcc) Mn (c/a = 1) behaves with two energetically degenerate magnetic states, namely the in-plane c(2×2) (compensated) and the [100] layered (uncompensated) AFM structures. 23,24 Since the compensated and uncompensated surface spin structures of the AFM layer were expected to lead to the collinear and noncollinear type of exchange coupling with the adjacent FM layer, respectively, it is possible to distinguish the preferred interfacial spin arrangement of the fcc-Mn layer in the FM/fcc-Mn bilayer by examining the characteristic of induced magnetization flipping of the FM film with the variation of Mn film thickness or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In an independent study, Yamada et al repeated the same measurement on a system with Mn on top of Fe(001), but found the domain-wall width to be nearly independent of the Mn thickness [19]. Similar frustrated spin configurations have also been reported in other systems [8,9,[20][21][22][23][24][25][26][27][28][29][30]. The frustration induced domain wall in nanorings is considered to lead to potential logic and memory applications [31].…”
Section: Introductionmentioning
confidence: 72%
“…4(c) and (d) the super-structure is shown in more detail, with the p(2 © 2) unit cell indicated by the square. From theoretical analyses 18,19) of the magnetic structures of Mn at (001) surfaces, it was found that there is only a tiny energy difference between the c(2 © 2) compensated and p(2 © 2) uncompensated magnetic configurations, with the c(2 © 2) being the most stable configuration. However, surface relaxations and/or reconstructions as well as structural imperfections might overcome this energy difference between the two configurations such that the p(2 © 2) uncompensated magnetic structure becomes the more stable configuration.…”
Section: Magnetic Ordermentioning
confidence: 99%
“…This magnetic configuration could also arise from the tetragonal distortion induced by the slight lattice mismatch between the substrate and the Mn film during the fcc to fct transition for thicker films. 19,20) …”
Section: Magnetic Ordermentioning
confidence: 99%